Empirical Patterns of Firm Growth and R&D Investment: A Quality Ladder Model Interpretation - Tor Jakob Klette; Zvi Griliches (Statistics Norway, Research Department, 1997)
We present a model of endogenous firm growth with R&D investment and innovation as the engine of growth. The objective of our analysis is to present a framework that can be used for microeconometric analysis of firm performance in high-tech industries. The model for firm growth is a partial equilibrium model drawing on the quality ladder models in the macro growth literature, but also on the literature on patent races and the discrete choice models of product differentiation. We examine to what extent the assumptions and the empirical content of our model are consistent with the findings that have emerged from empirical studies of growth, productivity, R&D and patenting at the firm level. The analysis shows that the model fits well empirical patterns such as (i) a skewed size distribution of firms with persistent differences in firm sizes, (ii) firm growth (roughly) independent of firm size (the so-called Gibrat's law) and (iii) R&D investment proportional to sales, as well as a number of other empirical patterns.
Keywords: L11; O32; D92; 330; Firm growth; R&D-investment; Gibrat's law; Product innovations